Reforming the posts : abandoning the monopoly-supported postal universal service obligation in developing countries - Kenny, Charles (Policy research working paper, 2005)
"The monopoly-supported universal service obligation (USO) is usually defended on the grounds that the monopoly allows for cross-subsidy in letter services that in turn allows universal access to a service of great importance to all. The author argues that letter delivery (as opposed to other services that may be provided by post offices) is not in universal demand in poor countries, that the size of the market in developing countries is such that USOs could not be met under the monopoly model, and that the monopoly carries heavy costs for sector development and consumer welfare. He proposes in the place of the postal USO a competitive approach involving universal access to a range of services that poor people have a need to access. Regarding reform of the incumbent, the author takes a preliminary first cut at examining the statistical relationship between postal performance (as measured by letters per capita allowing for income per capita), trust in the postal service, and postal efficiency, and finds a significant link between the three. The results suggest that reforms that improve postal efficiency and trust in the postal network will improve the performance of the postal network. The author suggests that there may be better uses of cross-subsidy from within the sector and government subsidy from without than supporting the inefficient delivery of a service rarely used by poor people. "--World Bank web site